Decision-making processes in organizational arrangements: An analysis in the light of population ecology and resource dependence - Cangussu, Melissa; Wandermurem, Luciane; Chester, David; Pessoa, Uajará (Seven Editora, 2023)
Increasingly, in contemporary organizations, discussions about decision-making have been occupying a relevant space, because the "decision maker" has the responsibility of making decisions for the organization, considering that the entire environment is transformed through decisions within the perspective of a theory: when in the light of population ecology, the organization adapts to the environment and when in the light of the theory of resource dependence, The organization prioritizes cooperative relations. This article, through a narrative bibliographic review, brings contributions to the theories of resource dependence and population ecology in the decision-making processes in the organizational arrangements, through an objective theoretical framework, which allows the reflection on decision-making processes, their relationship with organizational arrangements and theories, their interface with the most diverse areas, as well as their applicability in organizations. DOI:https://doi.org/10.56238/alookdevelopv1-054